2006
DOI: 10.1128/aem.00915-06
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Components of the Intestinal Microflora and Plasma Neuropeptide Levels of Feeding Lactobacillus delbrueckii , Bifidobacterium lactis , and Inulin to Adult and Elderly Rats

Abstract: The aim of this study was to compare the effects of the mixture of Lactobacillus delbrueckii subsp. rhamnosus strain GG, Bifidobacterium lactis Bb12, and inulin on intestinal populations of lactobacilli, bifidobacteria, and enterobacteria in adult and elderly rats fed the same (in quality and quantity) diet. The portal plasma levels of two neuropeptides, neuropeptide Y (NPY) and peptide YY (PYY), were also evaluated to assess the physiological consequences of the synbiotic treatment for the gastrointestinal (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 53 publications
5
21
0
3
Order By: Relevance
“…3B, 3C). Overall, our observation is consistent with the observations in some other long-term pre- and probiotic feeding studies where no dietary effects on food intake or body weight were found [39], [45]. Although epidemiological studies have linked higher fiber intake to lower body weight, it was likely a result of overall lower caloric density in a fiber-rich dietary pattern [46], [47].…”
Section: Resultssupporting
confidence: 92%
“…3B, 3C). Overall, our observation is consistent with the observations in some other long-term pre- and probiotic feeding studies where no dietary effects on food intake or body weight were found [39], [45]. Although epidemiological studies have linked higher fiber intake to lower body weight, it was likely a result of overall lower caloric density in a fiber-rich dietary pattern [46], [47].…”
Section: Resultssupporting
confidence: 92%
“…The small intestine as compared with large intestine has different metabolic function and its key physiological role is closely related with digestion and absorption of carbohydrates, proteins, and fats and short-chain fatty acids, respectively (36). Experimental studies in rats in which both luminal and tissue samples were used revealed a lowered number of total bacteria anaerobes, lactobacilli, enterobacteria, and bifidobacteria in proximal parts of small intestine (jejunum, ileum) and their substantially higher number in cecum and colon (37,38). At present time, however, the causal relationship between host metabolic efficiency and distinctive characteristic of microbial composition in upper part of intestinal tract is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this increase occurred immediately after full weaning in the current study, namely at a period during which the ATB-treated group still had a distorted microbiota compared to the CTL group. Bacteria and/or bacterial metabolites can regulate the expression of several gut peptides that control satiety [29]. Therefore, we can hypothesize that ATB treatment, by affecting the global ecosystem, favoured the development of one/some specific species or metabolite(s), which could produce alterations in gut peptides, resulting in a rise in food intake.…”
Section: Discussionmentioning
confidence: 99%